The viability of clob international after KLSE goes scripless - Abdul Rani Senin (2013)
KLSE is finally going scripless. This news had sent vibrations of uncertainty and apprehension across the Causeway to Singapore. Brokers and investors had expressed great apprehension and worries over the future of Clob. Will Clob be ‘clobbered’ as suggested by the media? Will the news signify the ‘death’ of Clob, and with it, the disappearance of the highly valued 60 % of its contribution to our SES turnover? In view of the above, this project was undertaken to analyse this issue in greater detail.